SIMILARITIES IN THE LYRICS OF ALISHER NAVOI AND HOFIZ KHWARAZMI: A COMPARATIVE ANALYSIS - Maksudova , Nigina (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Alisher Navoi (1441–1501) and Hofiz Khwarazmi (d. ca. 1403) are two of the most prominent poets in Central Asian literary history, whose lyrical works have significantly influenced the development of mystical and allegorical poetry in the region. Navoi, primarily writing in Chagatai Turkic, and Khwarazmi, composing mainly in Persian, both explore themes of divine love, self-reflection, and the human–spiritual relationship through intricate symbolic imagery. Despite linguistic and regional differences, preliminary studies suggest a remarkable overlap in thematic content and stylistic devices, indicating both a shared literary culture and possible direct influence. This study seeks to systematically examine the parallels between their lyric corpora using a combination of traditional literary analysis and computational methods, thereby providing empirical evidence for intertextual connections previously identified mainly through qualitative assessments.